2012
DOI: 10.1614/ws-d-11-00198.1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Plasticity in the Invasion of Crofton Weed (Eupatorium adenophorum) in China

Abstract: Phenotypic plasticity and rapid evolution are two important strategies by which invasive species adapt to a wide range of environments and consequently are closely associated with plant invasion. To test their importance in invasion success of Crofton weed, we examined the phenotypic response and genetic variation of the weed by conducting a field investigation, common garden experiments, and intersimple sequence repeat (ISSR) marker analysis on 16 populations in China. Molecular markers revealed low genetic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Many of the studied plant traits had PI v values higher than 50% in the field, and the mean PI v for every trait was 54 ± 4%, within the range recorded for other invasive plant species (Funk, 2008) and native species along wide latitudinal ranges (Chun-Can et al, 2014;Molina-Montenegro & Naya, 2012;Zhao et al, 2012). Our results are also consistent with previous studies on other polyploid…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Many of the studied plant traits had PI v values higher than 50% in the field, and the mean PI v for every trait was 54 ± 4%, within the range recorded for other invasive plant species (Funk, 2008) and native species along wide latitudinal ranges (Chun-Can et al, 2014;Molina-Montenegro & Naya, 2012;Zhao et al, 2012). Our results are also consistent with previous studies on other polyploid…”
Section: Discussionsupporting
confidence: 92%
“…However, our results show that they were kept at the individual level with some individuals from low latitudes (specially from Humboldt Bay) accumulating more Chl b and Car in the field and in the glasshouse and some individuals from high latitudes (specially from Vancouver Island) showing the opposite response. Thus, although environmental conditions, hybridization, and polyploidy largely determined plant traits in S. densiflora , our results point to a genetic or epigenetic component influencing certain traits due to changing selection pressures along a wide latitudinal range (Zhao et al., ). Ayres et al.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…At present, the weed is spreading north and west to drier, colder, higher regions, and has adapted to lower soil pH [3,10]. Former studies have focused on the factors that influence the spread of E. adenophorum, including environmental factors (e.g., elevation, temperature, precipitation, illumination and soil pH) [3,5,[10][11][12][13], biological factors (e.g., biomass of invaded areas, allelopathy, and competitive relationship) [4,5,7], genetic characteristics (e.g., rapid evolution and phenotypic plasticity) [8,14], and impact of human activities (e.g., land use patterns and road distribution) [3,5,7]. In regard to environmental factors, relatively high light intensity and high temperature in winter can contribute to the overwintering of E. adenophorum and help the weed to gain an advantage in competition with other species [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, trait plasticity and genetic variation were examined across 16 populations of Crofton weed (Eupatorium adenophorum) in China in a common garden experiment followed by intersimple sequence repeat (ISSR) marker analysis. This study revealed the presence of high phenotypic plasticity of functional traits despite having low genetically based variation (Zhao et al 2012).…”
Section: Towards a Unifying Research Frameworkmentioning
confidence: 73%